Implications of COVID-19 Pandemic on Evolution of Diabetes in Malaria-Endemic African Region - Samuel Acquah (Journal of Diabetes Research)
The coronavirus disease 2019 (COVID-19) pandemic continues to cause havoc to many countries of the globe, with no end in sight, due to nonavailability of a given vaccine or treatment regimen. The pandemic has so far had a relatively limited impact on the African continent, which contributes more than 93% of global malaria burden. However, the limited burden of COVID-19 pandemic on the African region could have long-term implications on the health and wellbeing of affected inhabitants due to its malaria-endemic status. Malaria causes recurrent insulin resistance with episodes of infection at relatively low parasitaemia. Angiotensin-converting enzyme 2 (ACE2) which is widely distributed in the human body is implicated in the pathogenesis of malaria, type 2 diabetes mellitus (T2DM), and COVID-19. Use of ACE2 by the COVID-19 virus induces inflammation and oxidative stress, which can lead to insulin resistance. Although COVID-19 patients in malaria-endemic African region may not exhibit severe signs and symptoms of the disease, their risk of exhibiting heightened insulin resistance and possible future development of T2DM is high due to their prior exposure to malaria. African governments must double efforts at containing the continued spread of the virus without neglecting existing malarial control measures if the region is to avert the plausible long-term impact of the pandemic in terms of future development of T2DM.